KERAGAAN GENOTIPE MUTAN BAAS SELEM GENERASI KEDUA (M2) HASIL IRADIASI SINAR GAMMA - Utama, Dio Alif; Suliartini, Ni Wayan Sri; Sudharmawan, A.A. Ketut (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
Research aims to determine changes in genotype characters that appear in the second generation Baas Selem (Oryza sativa L.) mutant (M2) resulting from gamma irradiation. This research was conducted from May to September 2021 in Nyur Lembang Village, Narmada District, West Lombok Regency, West Nusa Tenggara using an Expansion Randomized Block Design (RAK). The treatments used were 26 treatments consisting of 24 mutant plant genotypes and 2 control plants were tested using analysis of variance at the 5% level, then the significant results were tested further using the partition design RAK model. If there is a significant difference between the treatments, a follow-up test is carried out using the BNT test at the 5% level. Based on the results of a one-way analysis of variance for the characters tested from the 26 treatments (24 mutant plant lines namely G23, G87, G46, G65, G15, G34, G39, G5, G61, G54, G22, G74, G41, G72, G85 , G82, G39, G7, G141, G75, G62, G42, G81, and G21, 1 Baas Selem parent and 1 comparison variety, Inpago Unram, showed differences in genotypic characters on parameters of panicle length and number of empty grain per panicles. Keywords: Genotype Performance; Black Rice (Baas Selem), mutation induction